1991
DOI: 10.1046/j.1469-0705.1991.01020102.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of routine antenatal screening for congenital anomalies by ultrasound: The Belgian Multicentric Study

Abstract: United States and European consensus views differ on the place of routine ultrasound scans during pregnancy and the validity of such scans as screening tests for fetal malformations in the general population is still under debate. Four ultrasound laboratories from Obstetric and Gynecology departments of Belgian University hospitals and affiliated hospitals have conducted a prospective study from 1984 to 1989 to compare the anomalies discovered in ultrasonic screening of the fetus with the anomalies of the neon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
99
3
6

Year Published

1992
1992
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(126 citation statements)
references
References 0 publications
16
99
3
6
Order By: Relevance
“…Similarly, when the UEA was found in the setting of other non-upper extremity anomalies, pregnancy termination was more common. This aligns with previous studies showing that mothers are more likely to terminate a pregnancy in the setting of severe systemic anomalies [16][17][18][19].…”
Section: Itemsupporting
confidence: 92%
“…Similarly, when the UEA was found in the setting of other non-upper extremity anomalies, pregnancy termination was more common. This aligns with previous studies showing that mothers are more likely to terminate a pregnancy in the setting of severe systemic anomalies [16][17][18][19].…”
Section: Itemsupporting
confidence: 92%
“…Many reports on the eVectiveness of antenatal ultrasound diagnosis are from tertiary referral centres where high risk populations are screened. Few studies have reported on the eVectiveness of screening populations by routine (rather than targeted) ultrasound scans, [3][4][5][6] and the role of routine ultrasonography and its validity as a screening test for fetal malformation in a low risk population is still open to debate. 7 Of all congenital anomalies, neural tube defects (NTDs) are the easiest to identify prenatally.…”
mentioning
confidence: 99%
“…Furthermore, only 17% of fetal structural anomalies were detected before 24 weeks, as compared with an average of 52% (range, 21 to 84%) in European screening studies. [9][10][11][12][13][14] Due to late diagnosis any interventions for malformed fetuses, which could alter the perinatal outcome, were no possible. Another limitation in interpretation of these results is that the study population was at a very low-risk for perinatal problems.…”
Section: Introductionmentioning
confidence: 99%